DPANN symbiont of Haloferax volcanii accelerates xylan degradation by the non-host haloarchaeon Halorhabdus sp. - Oleg N. Reva; Violetta La Cono; Laura Marturano; Francesca Crisafi; Francesco Smedile; Manasi Mudaliyar; Debnath Ghosal; Elena A. Selivanova; Marina E. Ignatenko; Manuel Ferrer; Laura Fernandez-Lopez; Mart Krupovic; et al. (iScience)
Summary: This study examines a natural consortium of halophilic archaea, comprising xylan-degrading Halorhabdus sp. SVX81, consortium cohabitant Haloferax volcanii SVX82 (formerly H. lucentense SVX82), and its DPANN ectosymbiont Ca. Nanohalococcus occultus SVXNc. Transcriptomics and targeted metabolomics demonstrated that the tripartite consortium outperformed individual and the Halorhabdus sp. SVX81 with H. volcanii SVX82 bipartite cultures in xylan degradation, exhibiting a division of labor: the DPANN symbiont processed glycolysis products, while other members performed xylan depolymerization and biosynthesis of essential compounds. Electron microscopy and cryo-electron tomography revealed the formation of heterocellular biofilms interlinked by DPANN cells. The findings demonstrated that DPANN symbionts can interact directly with other members of microbial communities, which are not their primary hosts, influencing their gene expression. However, DPANN proliferation requires their primary host presence. The study highlights the collective contribution of consortium members to xylan degradation and their potential for biotechnological applications in the management of hypersaline environments.